DESAIN SIMULASI SISTEM KEAMANAN BERBASIS PLC DAN PENGENDALIAN KELEMBAPAN MENGGUNAKAN PID CASCADE PADA COLD STORAGE PASCAPANEN - Wibowo, Ellena Widya; Rusli, Moch.; Abidin, Zainul (Jurnal Mahasiswa TEUB, 2024)
Cold storage plays a crucial role in maintaining the freshness and quality of post-harvest products during distribution, which is key to reducing food loss and food waste. In Indonesia, food loss and food waste account for a total of 31% of food production, with economic losses amounting to approximately 550 trillion rupiah per year. One of the main challenges in cold storage is the optimal regulation of temperature and humidity, which can now be addressed with the use of environmentally friendlyhydrocarbon refrigerants. However, the potential hazards of hydrocarbon leakage, such as food contamination by carcinogeniccompounds like benzene, necessitate advanced safety systems. This study proposes the design of a comprehensive simulation system for safety and control in post-harvest cold storage using Schneider Modicon TM221 PLC and Weintek HMI. The humidity control system employs PID cascade to regulate the flow control of the humidifier, with PID tuning using the first Ziegler-Nichols method. This system aims to enhance cooling efficiency while ensuring the quality and safety of stored products. Through comprehensive simulation, this study is expected to provide deep insights into the interaction between control and safety systems and their contribution to reducing food loss and maintaining the quality standards of post-harvest products. Keywords: Cold Storage, Hydrocarbon Refrigerants, PLC, HMI, PID Cascade Control, Humidity Control.